EXPERIENCE OF THE COMPUTER CONFIGURATION PLANNING OF SURGICAL INTERFERENCE IN PATIENTS WITH CHRONIC FRONTAL SINUSITIS - Loburets, A.V.; Besshapochny, S.B.; Avrunin, V.G. (World of Medicine and Biology, 2017)
Modern forecasting methods are based on mathematical analysis of data and are implemented using electronic computing equipment. Computer configuration planning surgery in functional rhinology designed for prediction of functional results according to the operation of virtual modeling changes architectonics nasal cavity.The article represents the results of the computer configuration planning of the value of surgical interference of 56 patients who underwent inpatient treatment of chronic frontal sinusitis. The analysis of rhinomanometry indicators according to active posterior rhinomanometry (APR; M±m; kPa · s / l = Pa · s / m 3·106 ) and the research of aerodynamics of air resistance of nasal breathing were performed according to a spiral computer tomography (SCT; M±m; Pa · s / m 6·109) before and after surgery within the patients of the main group (n = 27) who underwent endonasal frontotomy correction intranasal structures (INS) and controls (n = 29) – by which was made the endonasal frontotomy. Extensive results of the study of two patients are presented separately. Statistically significant differences in the indicators of rhinomanometry before АAPR = 2,15±0,11 and after 4 weeks after surgery АAPR = 1,43±0,09 were observed in the patients of the main group who performed endonasal frontotomy with INS correction (p
Keywords: chronic frontal sinusitis; computer configuration planning; rhinomanometry; frontal sinus surgery